ChemInform Abstract: Targeted Manipulation of Metal‐Organic Frameworks to Direct Sorption Properties. Issue 50 (16th December 2014) - Schneemann, Andreas; Henke, Sebastian; Schwedler, Inke; Fischer, Roland A.
Abstract Review: 155 refs.